Market value of the firms and R&D investment: Theoretical overview and empirical estimation for the panel of countries - Dushko Josheski; Marija Magdinceva Sopova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The aim of this paper is to investigate the issue of R&D investment and the market value of the firm. This idea dating back from Arrow paper, later developed by Paul Romer but in the area of economic growth. Zvi Griliches (1979), first introduced the production function, which later would be used in a vast literature from this area (Market value of the firms and R&D investment). In the theoretical section of this paper we are describing Tobin's original model, and Abel's (1984) model, this models relates Tobin's quotient with intangible assets of the company. In the empirical part we develop cross-section time series model (Feasible Generalized Least Squares Model), for a panel of countries in Europe including UK and Turkey, in total of 11 panels. Later we test that model by estimating the marginal effects of R&D investment with Tobin's q on a small economy such as R. Macedonia. The results exert positive and statistically significant relationship between market value of the firms and R&D investment.
Keywords: D9; D46; 330; Tobin's q; R&D; knowledge absorption